Education on type 2 diabetes mellitus and its prevention in adolescents - Muhammad Anshari; Herda Ariyani; Muhammad Farid Ridho; Nurul Bayti; Waro Atunnisa (Community Empowerment, 2023)
The prevalence of Diabetes Mellitus based on a Doctor's Diagnosis in Population Age ≥ 15 Years according to the 2018 Riskesdas, in the province of South Kalimantan itself is 1.8%. Thus, education regarding risk factors for diabetes mellitus is needed. The purpose of this community service is to provide education to adolescents so that they are able to handle or prevent the occurrence of diabetes mellitus in themselves or their families and are able to utilize health services optimally. The activity is carried out in the form of online counseling. The results of the activity showed an increase in adolescent knowledge regarding diabetes mellitus, its prevention, and herbal ingredients that can be used as medicine.